The Relationship Between Activities of Visits to the Elderly Posyandu and The Elderly's Level of Independence - Aneng Yuningsih; Dara Indah KKH; Nandang Wahyu (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Background: Posyandu for the elderly is a service for the elderly community which aims to improve health and create a happy, healthy, independent and efficient old age. For elderly people who do not actively utilize health services at the elderly posyandu, their health condition cannot be monitored properly, so that if they experience a risk of disease due to a decline in body condition and the aging process, it is feared that this could have fatal and life-threatening consequences. Objective: This research aims to find out The relationship between active visits to elderly posyandu and the level of independence of elderly people at Posbindu Waluya Purwaharja 1, Banjar City. Research Method: This research is a quantitative correlation research with a survey research design. Time approach with a retrospective method. Results: from the results of the Chi Square statistical test, a P value of 0.000 is smaller than alpha 0.05. Conclusion: There is a relationship between the activeness of elderly posyandu visits and the level of independence of elderly people at Posbindu Waluya Purwaharja 1, Banjar City. Suggestion: Elderly people are expected to have greater awareness of the importance of elderly posyandu, the need for family support and new innovations to increase the attractiveness of elderly people to come to elderly posyandu